PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN PT. INSANI BARAPERKASA DI SAMARINDA - -, RAUDATUL JANNAH (EKONOMIA, 2014)
The objective of this study was to determine the effect of human resource development: education and training, non-training activities, promotion and motivation on employee performance at PT. Insani Baraperkasa in Samarinda.Analysis of the data used is multiple linear regression analysis to determine the effect of the independent variable (training & education, non-training activities, promotion and motivation) and the dependent variable (performance of employees) with a population and a sample of 85 permanent employees of PT. Insani Baraperkasa in Samarinda 2014.Based on data analysis, simultaneously that the variables of training and education, non-training activities, promotion and motivation have a significant effect on the performance of employees in PT. Insani Baraperkasa in Samarinda. While partially shown that the variable education and training  , promotion and motivation is that sigfnifikan affect employee performance in                                                    PT. Insani Baraperkasa in Samarinda while variable non-training activities do not affect the performance of the employee.